Professional engagement and quality of life among nursing professionals at a hospital, São Paulo - Brazil - Zogheib, Cristiane Maria Talala; Baptista, Patricia Campos Pavan; Lourenção, Daniela Campos de Andrade; Rached, Chennyfer Dobins Abi (O Mundo da Saúde, 2023)
This study aimed to analyze the association between engagement and the quality-of-life program of the nursing team. This was an exploratory, cross-sectional study, and 334 workers from the nursing team of a private hospital in the city of São Paulo participated. The following instruments were used: Worker Characterization Questionnaire, Work Engagement Scale, Workers' Perception of the quality-of-life program, and Score Sheet for Participation in the quality-of-life program. The global score of engagement at work presented an average of 4.62 points (SD=0.98 points), the highest level was observed in the dimension Dedication (average=4.93 points; SD=1.04 points), and the lowest in the Focus dimension (mean=4.33; SD=1.06). As for the quality-of-life program, it was possible to verify the adhesion of 152 nursing workers (45.5%). Regarding the perception of the institution's quality-of-life program, 83.92% have a positive perception. As for the circumstances that hinder participation, 52.95% are related to intrinsic factors of the worker, lack of time, difficulty in reconciling responsibilities outside the institution, simultaneous employment, and personal availability. This study group expressed a positive perception of the quality-of-life program, even identifying it as a stimulus for self-care and disease prevention, which are pillars for maintaining good health at work, and participants understand that it is a provided benefit in relation to other institutions, showing high levels of engagement with work.